The Effectiveness of Topical Insulin for Ulcer Healing: A Pilot Study: A Pilot Study - Adniana Nareswari; Ervina Rosmarwati; Merlina Wijayawati; Hastika Dwi Oktiningrum; Aulia Yasmin (Rumah Sakit Umum Daerah Dr. Moewardi, 2026)
Introduction Chronic ulcers continue to pose a major clinical challenge, contributing to significant morbidity and mortality. These conditions are frequently associated with diabetes, venous disorders, neuropathy, and other systemic illnesses. Conventional treatments often yield suboptimal results, encouraging investigation into alternative approaches such as topical insulin. This study aims to evaluate the effectiveness and safety of topical insulin in promoting ulcer healing. Method A pre-post interventional pilot study was conducted at Dr. Moewardi General Hospital from September to October 2024. Seven patients aged 40-80 years with grade II-III ulcers were treated with a topical insulin solution (10 IU insulin in 1 mL saline), applied once daily for 14 days. Ulcer size was measured on days 0, 7, and 14. Adverse effects were also monitored. Result Out of seven participants, three showed significant improvement in ulcer size (75-100% reduction), three showed mild to moderate improvement (8-26%), and one had no response. No local or systemic adverse events, including hypoglycemia, were observed. Factors such as limited patient mobility affected follow-up adherence. Discussion The findings suggest topical insulin enhances ulcer healing through mechanisms involving cell proliferation, angiogenesis, and anti-inflammatory effects, consistent with prior studies. However, the small sample size and loss to follow-up limit generalizability. Further trials are required to confirm its clinical utility. Conclusion Topical insulin appears to be a safe and potentially effective adjunct therapy for ulcer healing in both diabetic and non-diabetic patients. Larger-scale studies with control comparisons are needed to confirm its efficacy and optimize treatment protocols.